1996
DOI: 10.1097/00005373-199607000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and Clinical Relevance of Anisocoria-Craniotomy Latency for Epidural Hematoma in Comatose Patients

Abstract: In patients with an acute epidural hematoma, reducing the anisocoria-surgery interval below 90 minutes is significantly associated with a better outcome (p = 0.0238, Fisher's exact test).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
14

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 13 publications
1
42
0
14
Order By: Relevance
“…With delay to decompression, patients who suffered from brain herniation syndromes have increased rates of permanent disability and death (5). Some authors also reported that the critical time is not the time from injury, but the time from the onset of symptomatic brain compression (8,12,22,26). Haselsberger et al (12) reported that mortality rose from 17% to 65% and good recovery dropped from 67% to 13% when the time from the onset of coma to operation was more than 2 hours.…”
Section: █ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…With delay to decompression, patients who suffered from brain herniation syndromes have increased rates of permanent disability and death (5). Some authors also reported that the critical time is not the time from injury, but the time from the onset of symptomatic brain compression (8,12,22,26). Haselsberger et al (12) reported that mortality rose from 17% to 65% and good recovery dropped from 67% to 13% when the time from the onset of coma to operation was more than 2 hours.…”
Section: █ Conclusionmentioning
confidence: 99%
“…Pupils that are bilaterally unresponsive to light are associated with a high mortality (4,8,9,25,30,45). Patients with bilateral fixed and dilated pupils at surgery had 0-13% favorable outcome and 64-93% mortality rate (13,29,31,38,46).…”
mentioning
confidence: 99%
“…More than 70% of the extradural haematomas are associated with a skull fracture in adults but the figure is notably low in children 3 . Mortality ranges from 5-43% in various jurisdictions 4,5 . A high mortality rate is noted in the extremes of age, fewer than five years and those over 55 years of age 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Mortality ranges from 5-43% in various jurisdictions 4,5 . A high mortality rate is noted in the extremes of age, fewer than five years and those over 55 years of age 5 . Patients who present with a GCS of 3 with dilated and fixed pupils have specifically been reported to have a very high mortality rate 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation